Role of Novel Marker Discovered on Gastrointestinal Stromal Tumor 1 in Evaluation of Gastrointestinal Stromal Tumors - Abbas, Farhat; Besina, Syed; Farooq, Summyia; Bhat, Gull Mohammad; Ashraf, Shaziya; Latief, Muzamil (Indian Journal of Medical and Paediatric Oncology, 2019)
Background: Gastrointestinal stromal tumors (GISTs) are the most common mesenchymal tumors arising from myenteric ganglion cells, termed interstitial cells of Cajal. GISTs occur predominantly between 40 and 60 years of age. CD34 was the initially used for diagnosing GIST. Due to its low specificity for GISTs, CD34 was replaced by C-KIT, which is a reliable marker. However, 5% GISTs lack C-KIT expression. Recent studies have shown GIST1 (DOG1) to be a more sensitive and specific marker compared to C-KIT and CD34. Aims and Objectives: The aim was to study histomorphology characteristics and risk stratification of all cases previously diagnosed as GISTs, to evaluate these cases for CD117 and DOG1 expression by immunohistochemistry (IHC) and to see whether there was any advantage in using novel markers (i.e. DOG1) as compared to conventional (C-KIT) in GIST at our center. Materials and Methods: Fifty patients with histomorphologic or imaging impression of GIST were subjected to IHC using C-KIT and DOG1. Results and Conclusion: Of 50 cases 47 (94%) were positive for C-KIT, and all 50 (100%) cases were positive for DOG1. Hence, DOG1 was positive even in C-KIT-negative cases. Therefore, our study suggests that DOG1 should be added to workup of suspected cases of GIST along with C-KIT.
Keywords: Discovered on gastrointestinal stromal tumors 1; gastrointestinal stromal tumors; tumors